2013
DOI: 10.1177/1534734613477113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Homologous Platelet Gel on Healing Lower Extremity Wounds in Patients With Diabetes

Abstract: The treatment of chronic diabetic wounds remains complicated, despite new insight into the cellular and molecular basis of wound healing and cutaneous regeneration. A growing body of clinical trials has shown that platelet release has a notable effectiveness on refractory ulcer healing. However, patients with chronic diabetic ulcers usually have poor general health, and the large-volume blood absence required to produce autologous platelet-rich plasma often causes adverse effects. To overcome the limitation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…In this study, where we focused on wounds not associated with compromised blood and located in regions with good blood circulation, heterologous PRP may not induce faster wound reduction or alterations in tissue contraction during the repair process, similar to the results by Bauer et al 27 In contrast, some studies that presented superior effects of PRP studied chronic wounds in peripheral regions or in patients with some type of circulatory compromise 11,12,24,28 .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In this study, where we focused on wounds not associated with compromised blood and located in regions with good blood circulation, heterologous PRP may not induce faster wound reduction or alterations in tissue contraction during the repair process, similar to the results by Bauer et al 27 In contrast, some studies that presented superior effects of PRP studied chronic wounds in peripheral regions or in patients with some type of circulatory compromise 11,12,24,28 .…”
Section: Discussionsupporting
confidence: 67%
“…Despite the proven efficacy of autologous PRP in the aforementioned studies, another type of safe treatment can be useful when the patient's general condition prevents the use of his/her own blood for the production of this concentrate 11 .…”
Section: Introductionmentioning
confidence: 99%
“…21 Gui-Qiu Shan et al, in 2013 studied the effect of PRP on the healing of lower extremity chronic ulcers in which 21 patients with chronic ulcers are included in the study they concluded that, there no significance between type and site of ulcers in correlation with the rate of healing. 22 This supports the results we found in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Of course, many ongoing studies suggest great interest of the scientific community on this topic (Tables 5 and 6) [7,[89][90][91][92][93][94][95][96][97].…”
Section: Accepted Manuscriptmentioning
confidence: 99%